(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Breast cancer is a global health problem with significant impacts on women’s health worldwide(99). Understanding the mortality, prevalence, and incidence of breast cancer across geographic and demographic dimensions is an important epidemiological feature of breast cancer, as well as identifying risk factors that facilitate the development of appropriate public health policies(100). Breast cancer became the most diagnosed cancer among females worldwide in 2020, with approximately 2.26 million new cases reported. The global burden of breast cancer is projected to increase to more than 3,000,000 new cases annually by 2040. Globally, across ethnicities and regions, there are significant variations. Subjects and Methods: Over a period of seven months (from the beginning of October 2023 to the end of April 2024), 45 women were enrolled in the current study. The participants in the current study were divided into three groups based on their health status (women with breast tumors and healthy women), and depending on the type of tumor, the patients were divided into: women with malignant breast tumors and women with benign breast tumors. The first patients group consisted of 15 females with malignant breast tumors who participated in the work before starting chemotherapy and were followed up during receiving 3 consecutive doses of chemotherapy. The second patients group consisted of 15 females with benign tumors (enrolled as a pathological control group), while the healthy control group consisted of 15 females, their age ranged from 22 to 45 years. Sandwich enzyme linked immune sorbent assay (Sandwich ELISA) method was applied to evaluate C-Type Lectin Domain Family 8, member A (CLEC8A)and P-Selectin concentrations in the sera samples of the study individuals. Results: The result of the present work shows that there are no statistically significant differences in BMI in patients with different breast tumors when comparing the two groups together (p=0.090), as well as when comparing the group of patients with malignant tumors with the healthy control group (p=0.081), or when comparing the group of females with benign breast tumors with the healthy control group, the difference (p=0.957). The results showed a significant elevation in CLEC8A levels in the malignant tumor group comparison to the benign tumor group (p=0.000) as well as the health control group (p=0.000).Similarly, but with less statistical acceptability, a difference in CLEC8A concentration was observed when comparing the two control groups (patients with benign breast tumors and healthy females) together. When CLEC8A levels were evaluated during chemotherapy, a significant increase in the levels of this parameter was observed after receiving the first dose of chemotherapy, followed by a gradual decrease with the progression of doses. CLEC8A level was quickly decreased to a level lower than it was before starting treatment after receiving the second dose of chemotherapy. A significant decrease in the level of CLEC8A was observed after taking the last dose within the recommended course of chemotherapy compared to the levels of this lectin in the stage prior to starting the chemotherapy program. Statistical analysis using ANOVA test showed a significant increase (p=0.000) in P-Selectin levels in females with breast cancer when compared with benign breast tumor patients as well as healthy controls. When monitoring P-Selectin levels during the chemotherapy phase, a gradual decrease in the levels of this parameter was observed, proportional to the progress of the doses received by the patients, with a slight increase in the P-Selectin level recorded after the first dose of chemotherapy in only one patient, followed by a decrease in those values ​​with the progress of the treatment phases as in the rest of the samples. The results showed a significant (p=0.000) difference when comparing the P-Selectin level after receiving the last dose with its level before starting chemotherapy, as the levels of this parameter decreased to their levels in the healthy control group. Significant positive correlations were observed when studying the relationship between CLEC8A and P-Selectin in the group of patients with breast cancer (r = 0.712 at p<0.005) and the group of healthy females (r = 0.646 at p<0.005). The individual efficiency (sensitivity) of the criteria evaluated in the current study for distinguishing between cancerous and benign breast tumors reached the highest level (100%), while the study established the highest specificity (100%) for both CLEC8A and P-Selectin. Combined CLEC8A and P-Selectin.in this study showed a similar maximum sensitivity for each parameters (100%). Conclusion: Accordingly, the results of the present work indicate the possibility of using one of the two criteria, CLEC8A or P-Selectin, alone to infer a benign breast tumor, as the levels of these two criteria remain within their limits in the sera of healthy people, and thus it can be asserted that the detected tumor is a non-cancerous tumor.